2005
DOI: 10.1007/11590323_9
|View full text |Cite
|
Sign up to set email alerts
|

Laughter Abounds in the Mouths of Computers: Investigations in Automatic Humor Recognition

Abstract: Humor is one of the most interesting and puzzling aspects of human behavior. Despite the attention it has received in fields such as philosophy, linguistics, and psychology, there have been only few attempts to create computational models for humor recognition or generation. In this paper, we bring empirical evidence that computational approaches can be successfully applied to the task of humor recognition. Through experiments performed on very large data sets, we show that automatic classification techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(126 citation statements)
references
References 4 publications
2
121
0
3
Order By: Relevance
“…In a very similar study to ours [6] an analysis of the jokes in their corpus showed some possibly useful characteristics of jokes. For instance, they often contain human related words such as "you" or "I"; they often use negations, dirty words, antonymy etc.…”
Section: Stylesupporting
confidence: 72%
See 2 more Smart Citations
“…In a very similar study to ours [6] an analysis of the jokes in their corpus showed some possibly useful characteristics of jokes. For instance, they often contain human related words such as "you" or "I"; they often use negations, dirty words, antonymy etc.…”
Section: Stylesupporting
confidence: 72%
“…In our experiments we instead use quite low level information sources and see if enough hints can be gathered to determine if something is a joke or not without actually having any understanding of the meaning. Our work closely resembles the work in [6], where humor detection was treated as a text classification problem. Machine learning using content based information and some stylistic features present in many jokes gave results far above baseline performance.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…First, 150 one-liners were randomly selected from the humorous data set used in [13]. A one-liner is a short sentence with comic effects and an interesting linguistic structure: simple syntax, deliberate use of rhetoric devices (e.g.…”
Section: Datamentioning
confidence: 99%
“…One model (LSA on BNC) is trained on the British National Corpus (BNC) -a balanced corpus covering different styles, genres and domains. A second model (LSA on jokes) is trained on a corpus of 16,000 one-liner jokes, which was automatically mined from the Web [13].…”
Section: Corpus-based Semantic Relatednessmentioning
confidence: 99%